Volatile flavour constituent patterns of terras madeirenses red wines extracted by dynamic headspace solid‐phase microextraction - Perestrelo, Rosa Maria de Sá (2008)
A suitable analytical procedure based on static headspace solid-phase microextraction (SPME) followed by thermal desorption gas chromatography–ion trap mass spectrometry detection (GC–ITDMS), was developed and applied for the qualitative and semi-quantitative analysis of volatile components of Portuguese Terras Madeirenses red wines. The headspace SPME method was optimised in terms of fibre coating, extraction time, and extraction temperature. The performance of three commercially available SPME fibres, viz. 100 lm polydimethylsiloxane; 85 lm polyacrylate, PA; and 50/30 lm divinylbenzene/carboxen on polydimethylsiloxane, was evaluated and compared. The highest amounts extracted, in terms of the maximum signal recorded for the total volatile composition, were obtained with a PA coating fibre at 308C during an extraction time of 60 min with a constant stirring at 750 rpm, after saturation of the sample with NaCl (30%, w/v). More than sixty volatile compounds, belonging to different biosynthetic pathways, have been identified, including fatty acid ethyl esters, higher alcohols, fatty acids, higher alcohol acetates, isoamyl esters, carbonyl compounds, and monoterpenols/C13-norisoprenoids.